Five Year Plan Draft Proposals Volume I - Planning Commission (Planning Commission, 1978)
Meghalaya came into existence first as an Autonomous State within the State of Assam on April 2, 1970 and attained the full State-hood on January 21, 1972. It was formed initially with two hills districts, namely the United Khasi and Jaintia Hills and the Garo Hills, carved out of the State of Assam. It has now five administrative districts. Area and Population 2. Meghalaya covers a land surface of 22.509 square kilometres approximately which is 0.70 percent of the total area of India. Only four other States of India, namely Sikkim, Tripura, Nagaland and Manipur are smaller than Meghalaya in area. Its population in 1971 was 10,11,699 or 0.18 per cent of India’s total of 548 million. In terms of the population size, Meghalaya is one of the smallest in the country and only two Slates of India, namely, Sikkim and Nagaland, have smaller population.
Planning Department Government of Meghalaya